WALI DAN KARAMAH AMANG GAGA DI DESA UJUNG BARU, KECAMATAN BATI-BATI, KABUPATEN TANAH LAUT - Zakiah, Zakiah; Hakim, Abdul (Faculty of Ushuluddin and Humanities, 2016)
This research took up from perspective about the importance of discussing society opinion on Wali?s and the people are reputed as holy people or the people who has a special ability as a popular religion expression which still exists in the certain society. Paying homage by society to Wali?s are not only when they are still alive, but it also continue when they are died. Amang Gaga is one of them, he was respected and reputed as a Wali and he had a special ability (karamah) by people in Ujung Baru village, Bati-Bati, with the result that this research needs to be done. The questions of this research are (1) How does people opinion about Wali and Amang Gaga?s karamah? (2) What is level of guardian status of Amang Gaga as a Wali and his karamah according to tasawwuf?. Based on the findings that Amang Gaga is a Wali because his loyalty, his consistency and his karamah. The level of his guardian status is al-Quthub atau al-Ghawts. It means that the humans need him when they have difficulties, when he prayed to Allah, it would be answered Allah very fast. People pray to Allah through him as a medium. However, there is any evidence to show that Amang Gaga as the leader of Wali?s.